Efektifitas Penanganan Sampah oleh Dinas Lingkungan Hidup di Kelurahan Tamiang Layang Kecamatan Dusun Timur Kabupaten Barito Timur - Jessika Theresia Margareta; Arif Rahman Nugroho; Ghinia Anastasia Muhtar; M. Najeri Al Syahrin (INDO PUBLISHING, 2026)
The effectiveness of waste management is basically seen from the performance and cooperation of an agency in implementing the planned program. This study aims to identify the types of waste in Tamiang Layang Village, to find out the forms of waste management that have been carried out by the Environmental Agency, and to find out the effectiveness of waste management by the Environmental Agency of East Barito Regency in Tamiang Layang Village. The method used in this study is descriptive qualitative. Describing the conditions of the research area (field conditions) by means of direct observation, interviews with related parties (Environmental Agency), and documentation. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that (1) The types of waste in Tamiang Layang Village based on their nature, form, and source are organic and inorganic, generally in the form of solid, liquid, and biogas waste, which come from various sources such as households, markets, shops, stalls, and others; (2) Of the 4 forms of waste management, the East Barito Regency Environmental Service only collects and transports from the Temporary Disposal Site to the Final Disposal Site without any final processing. The final disposal system uses an open dumping system; (3) The conclusion from the research results shows that waste management carried out by the East Barito Regency Environmental Service is stated as